How England got to mandatory biodiversity net gain: A timeline - Alice Stuart; Alan Bond; Aldina M. A. Franco; Chris Gerrard; Julia Baker; Kerry ten Kate; Tom Butterworth; Joseph Bull; Jo Treweek (Ambio, 2026)
Biodiversity net gain (BNG) is a “net outcome” planning policy which aims for development projects to leave biodiversity in a better state than before they started. Understanding the origins and history of existing mandatory BNG is necessary to understand the drivers and barriers that have influenced the policy to date and could inform the development and implementation of future BNG policies. Biodiversity net gain legislation was first discussed in Parliament in England through the passage of the Environment Act (2021) and became a mandatory requirement for most terrestrial and intertidal developments in February 2024. The policy uses habitat attributes as a proxy for biodiversity and represented the widest reaching net outcome policy in the world at the point of its introduction. As such, it is expected to have a significant impact on future land use decisions in England. This paper uses a mixture of literature review and the knowledge of those involved in the early stages of this BNG policy development in England to present a timeline of the stages that have led to mandatory biodiversity net gain. In doing so, we highlight formative events and documents, as an important first step in understanding its history and understanding how this can be used to inform future biodiversity policy.

Brine reflux as a possible first order control on the alkali geochemistry of baseline sedimentary rocks in the Proterozoic North Australian Zinc Belt - Charles Gianfriddo; Stuart Bull (Precambrian Research, 2023)

Association mapping of malting quality traits in UK spring and winter barley cultivar collections - Mark E. Looseley; Luke Ramsay; Hazel Bull; J. Stuart Swanston; Paul D. Shaw; Malcolm Macaulay; Allan Booth; Joanne R. Russell; Robbie Waugh; William T. B. Thomas (Theoretical and Applied Genetics, 2020)
Key message Historical malting quality data was collated from UK national and recommended list trial data and used in a GWAS. 25 QTL were identified, with the majority from spring barley cultivar sets. Abstract In Europe, the most economically significant use of barley is the production of malt for use in the brewing and distilling industries. As such, selection for traits related to malting quality is of great commercial interest. In order to study the genetic basis of variation for malting quality traits in UK cultivars, a historical set of trial data was collated from national and recommended list trials from the period 1988 to 2016. This data was used to estimate variety means for 20 quality related traits in 451 spring barley cultivars, and 407 winter cultivars. Genotypes for these cultivars were generated using iSelect 9k and 50k genotyping platforms, and a genome wide association scan performed to identify malting quality quantitative trait loci (QTL). 24 QTL were identified in spring barley cultivars, and 2 from the winter set. A number of these correspond to known malting quality related genes but the remainder represents novel genetic variation that is accessible to breeders for the genetic improvement of new cultivars.

Age constraints on the hydrothermal history of the Prominent Hill iron oxide copper-gold deposit, South Australia - Bryan Bowden; Geoff Fraser; Garry J Davidson; Sebastien Meffre; Roger Skirrow; Stuart Bull; Jay Thompson (Mineralium Deposita, 2017)

Lewis Ponds, a hybrid carbonate and volcanic-hosted polymetallic massive sulphide deposit, New South Wales, Australia - Michael W. Agnew; Ross R. Large; Stuart W. Bull (Mineralium Deposita, 2005)

Numerical investigation of salinity in controlling ore-forming fluid transport in sedimentary basins: example of the HYC deposit, Northern Australia - Jianwen Yang; Stuart Bull; Ross Large (Mineralium Deposita, 2004)

Mass flow sedimentology within the HYC Zn?Pb?Ag deposit, Northern Territory, Australia: evidence for syn-sedimentary ore genesis - Tim Ireland; Stuart W. Bull; Ross R. Large (Mineralium Deposita, 2004)